POTENTIAL ROLE OF WILD CRUCIFERS IN THE PRESERVATION OF DIADEGMA EUCEROPHAGA HORSTMAN (HYMENOPTERA: ICHNEUMONIDAE), A PARASITOID OF THE DIAMONDBACK MOTH, PLUTELLA XYLOSTELLA LINNAEUS (LEPIDOPTERA: PLUTELLIDAE) - KARTOSUWONDO, UTOMO (BIOTROPIA, 2011)
Laboratory and field experiments were conducted to evaluate the potential role of two species of wild crucifers in the preservation of Diadegma eucerophaga Horstman, a parasitoid of the diamondback moth, Plutella xylostella Linnaeus. In the laboratory, D. eucerophaga developed quite well on P. xylostella larvae fed on leaves of two species of wild cruciferous plants, Nasturtium heterophyllum BL. and Cardamine hirsuta L. These wild crucifers may serve as food and oviposition sites for P. xylostella. In the field, N. heterophyllum and C. hirsuta planted adjacent to insecticide-treated cabbage plots provided refuge for D. eucerophaga parasitoids.